2023
DOI: 10.4014/jmb.2310.10028
|View full text |Cite
|
Sign up to set email alerts
|

Specific Alternation of Gut Microbiota and the Role of Ruminococcus gnavus in the Development of Diabetic Nephropathy

Jinni Hong,
Tingting Fu,
Weizhen Liu
et al.

Abstract: In this study, we aim to investigate the precise alterations in the gut microbiota during the onset and advancement of diabetic nephropathy (DN) and examine the impact of Ruminococcus gnavus ( R. gnavus ) on DN. Eight-week-old male KK-Ay mice were administered antibiotic cocktails for a duration of two weeks, followed by oral administration of R. gnavus for an additional eight weeks. Our study revealed significant changes in the gut microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…44,45 Recent studies have found that the abundance of Ruminococcus is significantly higher in rats with diabetic nephropathy, and the administration of Ruminococcus gnavus aggravated the condition. 46 The abundance of Ruminococcus was also significantly increased in folate-induced AKI mouse models. 47 However, there are contrasting results from studies on the gut microbiota in chronic kidney disease and ischemia-reperfusion leading to AKI, and the results show reduced abundance of Ruminococcus.…”
Section: Discussionmentioning
confidence: 97%
“…44,45 Recent studies have found that the abundance of Ruminococcus is significantly higher in rats with diabetic nephropathy, and the administration of Ruminococcus gnavus aggravated the condition. 46 The abundance of Ruminococcus was also significantly increased in folate-induced AKI mouse models. 47 However, there are contrasting results from studies on the gut microbiota in chronic kidney disease and ischemia-reperfusion leading to AKI, and the results show reduced abundance of Ruminococcus.…”
Section: Discussionmentioning
confidence: 97%